EUTHANASIA AS A REASON FOR UNWORTHINESS TO INHERIT - Milović, Jovana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The provision of the right to a dignified death within the Pre-Draft Civil Code of the Republic of Serbia has again actualized the discussions on its legalization. Within the framework of inheritance legislation, there are discussions regarding the place of euthanasia among the reasons for unworthiness to inherit. In most legislations, euthanasia is still a criminal offense and on that basis the reason for unworthiness to inherit. In legal systems where euthanasia is allowed, this procedure is completely performed by a doctor. Heirs are not involved in its implementation. Accordingly, euthanasia is not mentioned as a reason for the unworthiness of the heir. The solution proposed in the Preliminary Draft of the Civil Code of the Republic of Serbia was generalized and left for further discussion. Until the proposed solution is adopted in this or a slightly modified form, active euthanasia will be a reason for unworthiness to inherit, while passive euthanasia could be discussed within some other legally prescribed reasons for unworthiness.
Keywords: euthanasia; deprivation of life out of compassion; heir; unworthiness to inherit; premeditated murder